Makna Tari Baris Dadap dan Tari Baris Panah di Desa Kertha Mandala, Kecamatan Abang, Kabupaten Karangasem - Anak Agung Ayu Mayun Artati; Ni Luh Putu Nila Yuliantini; Anak Agung Oka Adnyana (Departement of Mathematics Education, 2023)
This study aims to be able to understand and explain the existence of the Baris Dadap Dance and the Baris Arrow Dance in Kerta Mandala Village. This research was conducted using qualitative methods. The data sources for this research were the performance of the Baris Dadap Dance and the Baris Panah Dance itself, the elders, the administrators of the Maksan Ngis Temple, community leaders, the Maksan Ngis Temple community, Kerta Mandala Village, who were selected based on purposive sampling and snowball techniques. All data that has been collected through observation, interviews, and literature studies is analyzed using structural-functional theory and religious theory. The results showed that the Baris Dadap Dance and the Baris Panah Dance which are performed every six months, to be precise at every Tumpek Kuningan at Maksan Ngis Temple, Kerta Mandala Village, are ceremonial dances. This can be seen from the process of presentation, the variety of movements, the structure of the performance, the fashion make-up, and the musical accompaniment of the performance. Until now, the people of Kerta Mandala Village continue to preserve these two sacred dances because these dances function as ceremonial dances which are presented at every piodalan ceremony of Ida Meraga Taksu Baris Dadap and Baris Panah in Kerta Mandala Village. Apart from functioning as ceremonial dances, the two ceremonial dances are preserved because they function as binders of social relations for the local community.